SENI DALAM DIMENSI EKOLOGI: PERAN INSAN SENI DALAM ADVOKASI ISU LINGKUNGAN - Anggrian, Mayang; Iksan, Nur (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2022)
Art and its crosses in ecological areas have the opportunity and potential to help advocate environmental issues in the community. However, the art of ecology and advocacy about it has not been done by many artists. Even artwork and environmental advocacy are less popular and desirable in the art ecosystem because it doesn’t intersect with the practical economy of artists. In fact, referring to the increasingly critical global ecological situation, it is currently necessary to make sustainable efforts to build community eco consciousness. This research then questioned about the motives of art activist doing artwork with environmental theme, as well as their role in advocating environmental issues in society. Furthermore, this research also examines how the impact of artistic work with the environmental theme on the surrounding community. This is interesting because the various environmental advocacy efforts that have been caried out by these artist have been responded to by various dynamics in society, and it can be seen if people of the arts can play a unique role in environmental advocacy. In the end the qualitative descriptive method used in this study found a number of certain pattern about the motivation, role, and impact of environmental art work that has been carried out by artists in the local community. Based on this research environmental advocacy and artistic work have become a catalyst for the appreciation of eco-consciousness of the surrounding community. The position of the arts is quite strategic as agent of change.